Chronic obstructive pulmonary disease and obstructive sleep apnoea—the overlap syndrome - McNicholas, Walter T. (Journal of Thoracic Disease; Vol 8, No 2 (February 01, 2016): Journal of Thoracic Disease [(dedicated to) the International Conference: Clinical Update Sleep 2016], 2016)
Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnoea (OSA) are highly prevalent disorders and the co-existence of both disorders, termed the overlap syndrome, affects at least one per cent of the adult population. Patients with the overlap syndrome typically experience more pronounced nocturnal oxygen desaturation and there is a high prevalence of pulmonary hypertension in such patients. Recent evidence suggests that the prevalence of each disorder together is higher than might be predicted by simple prevalence statistics, although the evidence is not clear-cut in this regard. Sleep itself can have several negative effects in patients with COPD. Sleep quality is diminished with reduced amounts of slow wave and rapid-eye-movement (REM) sleep, which may contribute to daytime symptoms such as fatigue and lethargy. Furthermore, normal physiological adaptations during sleep that result in mild hypoventilation in normal subjects are more pronounced in COPD, which can result in clinically important nocturnal oxygen desaturation. Management of sleep disorders in patients with COPD should address both sleep quality and disordered gas exchange. Non-invasive pressure support is beneficial in selected cases, particularly during acute exacerbations associated with respiratory failure, and is particularly helpful in patients with the overlap syndrome. There is limited evidence of benefit from pressure support in the chronic setting in COPD patients without OSA.